Pengujian Tahanan Kontak Pemutus Tenaga 70 KV Di Gardu Induk Rengas Dengklok Karawang - Muhammad Mursal Fikri; Insani Abdi Bangsa; Ulul Ilmi (Universitas Islam Lamongan, 2021)
The increasing demand for electric power every year demands to provide reliable electric power. One of the important parts to support the reliability of the electric power system is the substation. Substation is a subsystem of the electric powerdistribution system. One of the materials from the substation is a Circuit Breaker (CB) which is a switch that is used to open or close an electrical circuit under load conditions, and is able to connect or disconnect electrical circuits during normal conditions or when a fault current occurs. The CB needs to be maintained to maintain the reliability of CB. This research aims to determine the value of contact resistance in CB. In this research, data were collected from the last 2 periods of maintenancecarried out at the Rengas Dengklok Substation, PT. PLN (Persero) Karawang.Overall with the maintenance and testing of CB contact resistance, the reliability ofthe CB is maintained and can work normally